Determinants of Commercial Bank Profitability: Evidence from Japan - LIANG, SHUQI (2020)
This study aims to apply the System Generalized Method of Moments (SGMM) estimator to examine the implications of bank-specific, industry, and macroeconomic determinants on the Japanese bank profitability over 2008-2018, based on unbalanced panel data of 134 Japanese commercial banks. Meanwhile, ROAA, ROAE, and NIM are selected as three dependent variables of profitability. Furthermore, equity-to-total assets ratio, the loan-loss reserve to total loans, total assets, loans-to-deposits are used as independent variables to represent the bank's capital adequacy ratio, credit risk, bank size, and liquidity, respectively. The external variables include concentration, GDP growth rate, and inflation rate. The empirical results are consistent with the expected outcomes report that size, asset adequacy, inflation, and GDP growth rate are positively and significantly associated with ROAA and ROAE. However, the concentration is adversely connected with two dependent variables. Moreover, NIM findings show that credit risk and asset adequacy are actively correlated with NIM at 5% and 1% significant levels. In comparison, there is an inverse correlation between NIM and size, inflation with a 5% level. However, it seems that neither liquidity is significant for three indicators of profitability, which means the correlation of liquidity with the Japanese banking sector could not be identified during the research period.